The Expert Perception on Development and Usability of Teaching Aids ‘Kit’ Mini Model (Cage System) for Aquaculture Course - Hafizi Harun; Zalina Ismail; Asilah Abdul Mutalib; Zahidah Ab Latif; Shaibatul Islamiah Che Man (Universitas Ahmad Dahlan, 2021)
The increasing technology as changed the learning methods nowadays which clearly presents a new challenge to educators. Moreover, following the COVID-19 pandemic that hit the world at this time completely inhibits the teaching and learning process to be done entirely online. This clearly presents difficulties to teachers and students, as there are subjects that require practice to improve skills and better understanding. Among the limited access for teachers during the online learning and teaching process is that teachers can only explain and display pictures and show videos. At the same time, students need skills and understanding related to a subject studied. Also, students may not be able to accurately identify the types of systems found in the subjects studied. For example, for aquaculture subjects, the process of online teaching and learning can actually be done. However, this subject also requires practical and field work for students. In aquaculture subjects, in particular, teaching aids play an important role in understanding the cage farming system concept in the teaching process because there are various farming systems used in the aquaculture industry. The development of teaching aid is a crucial phase to make sure the teaching aids develop in accordance with the objectives and topics learning. Therefore, it is important to have an expert perception of the development and usability of the Teaching Aids kit mini model (Cage system). This study consisted of 9 experts as an evaluator consisting of experienced lecturers in the technical field of Faculty Technical. This study uses a quantitative assessment method (questionnaire).Â Â A set of questionnaires was distributed to the experts to obtain the required information and data. All data obtained were analyzed using computer software' Statistical Package For Social Science SPSS version 24 to obtain the frequency, percentage and mean through descriptive statistic. The study's findings show that the level of experts' perception ofÂ â€œTeaching Aids kit mini model (Cage system) development and usability is necessary and positive. The study's conclusion illustrates the need for the development of a teaching aids kit mini model (cage system) for teachers to increase the level of understanding and skills of individual students in the teaching and learning process for aquaculture subjects.